The impact mechanism of green technology innovation on urban green development: Evidence from Central China - Peixu, Wang; Talib, Zunirah Mohd; Rashid, Omar b. Abdul; Keat, Ooi Boon (Edelweiss Applied Science and Technology, 2025)
In order to further promote urban green development in Central China, the research uses panel data from 80 cities in Central China from 2011 to 2022 as a sample and employs the linear regression method, mediating effect, and threshold effect to empirically test the impact mechanism of green technology innovation on urban green development in Central China. The results show that: first, green technology innovation significantly promotes urban green development, and the conclusion still holds when considering endogeneity. Second, the regional heterogeneity test found that the differences in resource endowments among provinces lead to significant differences in the impact of green technology innovation on urban green development. Third, the mediating effect found that digital inclusive finance and industrial structure upgrading both play partial mediating roles between green technology innovation and urban green development. Fourth, the threshold effect found that urban environmental infrastructure investment has a positive single threshold effect between green technology innovation and urban green development. This paper not only enriches the research on urban green development at the academic level but also provides reference value for the sustainable development of cities in other developing countries and regions. The objective of this study is to explore how to promote the green development of cities in Central China from the perspective of green technology innovation and to provide a reference for other developing countries and regions. In this topic, the main concepts and theories that underpin the research are presented. First, the concept of sustainable development lays the main tone of this study. Second, Schumpeter’s innovation theory provides theoretical support for establishing the connection between green technology innovation and urban green development. The methodology adopted for this research comprises the entropy method, panel multiple linear regression model, mediation effect model, and threshold effect model. The original data used in this study are authoritative secondary data from the official statistical yearbooks of various provinces in Central China. The results obtained revealed that green technology innovation has a significant positive promoting effect on urban green development in Central China, and digital inclusive finance and upgrading of industrial structure have significant partial mediating roles in the process of green technology innovation promoting urban green development in Central China. The threshold effect found that urban environmental infrastructure investment has a significant single threshold effect in the process of green technology innovation promoting urban green development in Central China. In the discussion section, these results are contextualized in light of the theoretical framework, highlighting the implications and relationships identified. Possible discrepancies and limitations of the study are also considered in this section. The practical and theoretical implications of this research are discussed, providing insights into how the results can be applied or influence practices in the field of urban green development. First, this study provides new ideas for policymakers in urban green development in Central China. Second, this study provides a reference for urban green development in other developing countries and regions. These implications could encompass green technology, green lifestyle, green production, and green industry, etc. This study contributes to the literature by considering new ideas for green technology innovation, as well as the intermediary effect of digital inclusive finance and the threshold effect of green investment. The relevance and value of this research are evidenced by the fact that green technology innovation, digital inclusive finance, and green investment provide new ideas for policymakers and enterprises for urban green development.